Tanggap Pertumbuhan dan Hasil Tomat yang Diinokulasi FMA dalam Pengendalian Fusarium (Fusarium oxysporum f.sp. lycopersici) - Cahterine Pentury; Antonius Suparno; Eko Martanto (Program Pascasarjana Universitas Papua, 2018)
The Wilt in tomato plants is caused by Fusarium oxysporum sp. Lycopersici. Fusarium oxysporum is soil borne which causes considerable losses. FMA as a biological agent provides an alternative opportunity to control root diseases such as fusarium. The purpose of this study was to study the treatment of FMA inoculation which is appropriate while controlling the damage of tomato plants caused by fusarium. The research design used was the experimental method in Completely Randomized Design. The results showed that the treatment of mycorrhizae inoculated one week before planting and continued with fusarium inoculation at the time of planting showed good results in inducing the resistance of tomato plants to fusarium disease. This is evidenced by root colonization in tomato plants by 53% and the average intensity of attacks by 3.14%. The mycorrhizal treatment inoculated one week before planting and followed by fusarium inoculation at planting also showed good results in increasing the growth of tomato plants compared to other treatments applied by mycorrhiza.